Magnetic Properties of Ln2Zr2O7 (Ln = Ho and Er) Compound - Rani, Priyanka; Thakur, A.N.; Raghuvanshi, Pooja; Kumar, A. (Asian Journal of Chemistry, 2011)
The heavy rare earth zirconate compound Ln2Zr2O7 (where Ln = Ho, Er) were prepared by solid state reaction method. The prepared compounds have been characterized by XRD, DT, TG and DTG. XRD studies suggest the formation of single phase orthorhombic structure at room temperature. We describe magnetic susceptibility measurements of the compounds at high temperature. In these compounds magnetism arises from the rare-earth ions, while Zr is non magnetic. All the compounds show antiferromagnetic behaviour at low temperature and obey Curie-Weiss law.